Outburst of pest populations in rice-based cropping systems under conservation agricultural practices in the middle Indo-Gangetic Plains of South Asia - Kumar, Rakesh; Choudhary, Jaipal Singh; Mishra, Janki Sharan; Mondal, Surajit; Poonia, Shishpal; Monobrullah, Mohammad; Hans, Hansraj; Verma, Mausam; Kumar, Ujjwal; Bhatt, Bhagwati Prasad; Malik, Ram Kanwar; Kumar, Virender; et al. (Springer, 2022)
Conservation agriculture (CA), which encompasses minimum soil disturbance, residue retention either through crop residue, or cover crops and crop diversification-based crop management practices can modify the status of pest dynamics and activities under the changing climatic scenarios. CA has been advocated extensively to optimize the use of available resources, maintain the environmental quality, enhance crop productivity, and reduce the climate change impacts. Information related to the impacts of long-term CA-production systems under rice-based cropping systems on pest status is lacking, particularly in middle Indo-Gangetic Plains (MIGP). Under CA, puddling is completely avoided, and rice is directly sown or transplanted to maintain better soil health. Different sets of experimentations including farmers practice, partial CA and full CA (CA) as treatments in rice-based cropping systems, were established from 2009, 2015 and 2016 to understand the long-term impacts of CA on pest dynamics. In this study, direct and indirect effects of tillage (zero, reduced and conventional tillage), residue retention and cropping sequences on abundance and damage by pests were investigated. After 4–5 years of experimentation, populations of oriental armyworm [Mythinma (Leucania) (Pseudaletia) separata (Wlk.)] in wheat, mealybug [Brevennia rehi (Lindinger)] and bandicoot rat [Bandicota bengalensis (Gray)] in rice were found to increase abnormally in CA-based production systems. Conventionally tilled plots had a significant negative effect while residue load in zero-tilled plots had a significant positive effect on larval population build-up of M. separata. Zero tillage had a higher infestation of mealybug (52–91% infested hills) that used grassy weeds (Echinochloa colona, Echinochloa crusgalli, Cynodon dactylon, Leptochloa chinensis and Panicum repense) as alternate hosts. Cropping sequences and no disturbance of soil and grassy weeds had higher live burrow counts (4.2 and 13.7 burrows as compared to 1.47 and 7.53 burrows per 62.5 m2 during 2019–2020 and 2020–2021, respectively) and damaged tillers (3.4%) in CA-based practices. Based on the present study, pest management strategies in CA need to be revisited with respect to tillage, residue retention on soil surface, grassy weeds in field and cropping sequences to deliver the full benefits of CA in MIGP to achieve the sustainable development goals under the climate change scenarios.